PRIMARY SCHOOL TEACHERS’ PERCEPTIONS OF AND PRACTICES IN THE SELECTION AND DEVELOPMENT OF ENGLISH LEARNING MATERIALS - Noni, Nurdin (LITERA, 2016)
PRIMARY SCHOOL TEACHERS’ PERCEPTIONS OF AND PRACTICES IN THE SELECTION AND DEVELOPMENT OF ENGLISH LEARNING MATERIALS Nurdin Noni FBS Universitas Negeri Makassar email: nurdinnoni@yahoo.com Abstract This study aims to describe: (a) teachers’ profiles, (b) teachers’ perceptions of the use of learning materials, and (c) practices in the selection and development of English learning materials by primary school teachers in Makassar City. The study used the descriptive method by involving primary school teachers of English. The sample consisted of 15 primary school teachers of English, randomly selected from two clusters, namely the city center and the suburb. The data were collected using a questionnaire. The results and discussion include the English teachers’ profiles, perceptions of, and practices in the selection and development of English learning materials for primary schools. In general, it can be concluded that the perceptions of primary school teachers of English are in line with their practices in the selection and development of learning materials. Keywords: perception and practices, selection and development of English learning materials PERSEPSI DAN PRAKTIK GURU SEKOLAH DASAR DALAM PEMILIHAN DAN PENGEMBANGAN MATERI PEMBELAJARAN BAHASA INGGRIS Abstrak Penelitian ini bertujuan mendeskripsikan: (a) profil guru, (b) persepsi guru terhadap penggunaan materi pembelajaran, dan (c) praktik pemilihan dan pengembangan materi pembelajaran bahasa Inggris oleh guru sekolah dasar di Kota Makassar. Metode yang digunakan adalah metode deskriptif dengan melibatkan 15 guru bahasa Inggris sekolah dasar yang dipilih secara acak dari dua klaster, yakni pusat kota dan daerah pinggiran kota. Data dikumpulkan dengan menggunakan angket. Hasil dan pembahasan meliputi profil guru bahasa Inggris, persepsi, dan praktik pemilihan dan pengembangan bahan ajar bahasa Inggris untuk sekolah dasar. Secara umum dapat disimpulkan bahwa persepsi guru bahasa Inggris sekolah dasar memiliki kesesuaian dengan praktik yang mereka lakukan dalam pemilihan dan pengembangan bahan ajar. Kata kunci: persepsi dan praktik pembelajaran, pemilihan dan pengembangan materi pembelajaran and setting